Children’s Internet Addiction, Family-to-Work Conflict, and Job Outcomes: A Study of Parent–Child Dyads1 - Venkatesh, Viswanath; Sykes, Tracy Ann; Chan, Frank K. Y.; Thong, James Y. L.; Hu, Paul Jen-Hwa (MIS Quarterly, 2019)
This paper examines the role of parenting behaviors in influencing children’s Internet addiction and the consequences of children’s Internet addiction on parents’ job outcomes. First, we draw on attachment theory to theorize that five parenting behaviors (i.e., parental control, monitoring, unstructured time, dissuasion, and rationalization) affect children’s Internet addiction and their effects are moderated by the children’s views of parent–child attachment. Second, we draw on research on the work–family interface to theorize that children’s Internet addiction affects parents’ job outcomes (i.e., job satisfaction, organizational commitment, and work exhaustion) and the effects are mediated by family-to-work conflict. We tested our hypotheses using an integrated research approach that includes quantitative and qualitative data. We conducted an online survey to collect quantitative responses from 776 parent–child dyads. The results of our model showed that the effects of parenting behaviors on children’s Internet addiction, except for dissuasion, were moderated by the children’s views of parent–child attachment. Also, family-to-work conflict mediated the effects of children’s Internet addiction on parents’ job satisfaction, organizational commitment, and work exhaustion. We collected qualitative data via interviews from 50 parents to cross-validate the results from the quantitative study.